1983
DOI: 10.1111/j.1600-0447.1983.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of mianserin to affect autonomic function in the pupils of depressed patients

Abstract: The autonomic effects of mianserin were tested in seven depressed patients by comparing pupillary responses to adrenergic and cholinergic agonists before and after treatment. Mianserin failed to affect pilocarpine-evoked miosis and tyramine- or phenylephrine-evoked mydriasis, despite adequate plasma levels of the drug. There was, however, a significant reduction in resting pupillary size after 1 and 3 weeks of treatment: this could result either from a central action, or from interactions at receptors other th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Responses to adrenergic agents did not distinguish groups. Dilsaver & Greden (50) concluded desipramine produced cholinergic system supersensitivity in depressed subjects. Twenty-one days of desipramine treatment, but not 7, produced enhancement of the miotic response to pilocarpine (51, 52).…”
Section: Pharmacological Perturbation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses to adrenergic agents did not distinguish groups. Dilsaver & Greden (50) concluded desipramine produced cholinergic system supersensitivity in depressed subjects. Twenty-one days of desipramine treatment, but not 7, produced enhancement of the miotic response to pilocarpine (51, 52).…”
Section: Pharmacological Perturbation Strategiesmentioning
confidence: 99%
“…The ability to establish correlations among clinical or phenomenological variables (mood, affect, psychomotor function, hedonia) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), physiological measures (e.g., dexamethasone suppression test (DST) results, absolute post-dexamethasone plasma cortisol, l3-endorphin, and adrenocorticotropin hormone (ACTH) levels (32,33,(37)(38)(39)(40), polysomnographic parameters ( R E M latency and density, etc.) (41)(42)(43)(44)(45)(46)(47)(48), pupillometric data (49)(50)(51)(52), biochemical indices (phospholipid turnover, rate of cyclic GMP generation) (52-5 8 ) , and B,,,,,, and K,, for binding of muscarinic receptor ligands in viva (59-70) enhances experimental versatility. It also provides a powerful means of studying the same phenomenon from the multiple aspects which define or determine it.…”
Section: Pharmacological Perturbation Strategiesmentioning
confidence: 99%
“…Additional data suggests that DMI produces cholinergic system supersensitivity in man and animals. Chronic treatment with DMI enhances the miotic response to pilocarpine in depressed subjects (Dilsaver and Greden, 1983;Shur et al, 1983). Nomura et al (1982b; reported that treatment with DMI, 10 zag/kg ip twice daily increases the negative ionotropic effects of acetylcholine and produces an exaggerated increase in the activity of ornithine decarboxylase in response to a cholinergic agonist.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Changes in pupil diameter, in man, can be measured by a photographic method (Sneddon, 1968). Dose-response curves have been published for the miotic response to pilocarpine and the mydriatic response to phenylephrine (Shur et al, 1983) and to tyramine (Peet et al, 1980).…”
Section: Introductionmentioning
confidence: 99%